Dampak Virus Corona (Covid-19) Terhadap Sektor Kelautan dan Perikanan : A Literature Review - Mery Nova Sari; Fransiska Yuliasara; Mahmiah (Universitas Hang Tuah, 2020)
The Corona Virus Pandemic (Covid-19) shook mankind around the world including Indonesia in early 2020. The coronavirus outbreak and the issuance of regulations on PSBB (Large-Scale Social Restrictions) make changes in community activities outside the home, whether it's job, education and even transportation. The decline in activity if it lasts a long time will certainly have an impact on the decline in people’s daily income, especially local fishermen and fish farmers. Not only that, some fish storage sheds (cold storage) occurs accumulation of fish or over stock because it can not be supplied outside the area as usual. This article is intended to discuss the impact of Covid-19 on the marine and capture fisheries sector. The results of the literature study show the impact of Covid-19 on the marine and fisheries sector, namely the decline in fish prices in some regions by up to 50% due to declining demand such as some fish export companies closed, many hotels and restaurants closed which are the main buyers of fish and seafood.